Evaluasi Penerapan Cara Produksi Pangan Olahan yang Baik (CPPOB) di Departemen Bakery PT XYZ Ketapang - Panca Wardanu, Adha; Andriani, Sri; Uliyanti, Uliyanti (Politeknik Negeri Ketapang, 2023)
This study aims to evaluate the implementation of CPPOB at PT XYZ in improving product quality and safety. This qualitative descriptive study consists of several stages: planning, data collection, analysis, and reporting. The collected data consists of primary and secondary data obtained through interviews and observations. Interviews were conducted with PT XYZ management, production personnel, and quality staff to identify the main aspects evaluated. In contrast, observations were conducted directly at the company's premises to monitor the production process from raw material acceptance to final product packaging. Assessment of CPPOB implementation is based on compliance with the Regulation of the Minister of Industry of the Republic of Indonesia Number: 75/M-IND/PER/2010 regarding guidelines for good manufacturing practices for processed foods. The results of the CPPOB implementation evaluation at PT XYZ have been conducted well, with a compliance percentage reaching 98% and non-compliance at 2%.